13 Oral P2Y12 inhibitor therapy in heat-PPCI: results of a pre-specified sub-study examining early effects on platelet aggregation and clinical events. (24th April 2016) - Shahzad, Adeel; Khanna, Vikram; Kemp, Ian; Mars, Christine; Cooper, Rob; Roome, Claire; Wilson, Keith; Curzen, Nick; Stables, Rod
Abstract : Background: HEAT-PPCI compared bivalirudin and heparin in patients undergoing primary percutaneous coronary intervention. All patients received pre-procedural oral anti-platelet therapy, initially prasugrel (Pr) with some use of clopidogrel (C). Later, routine therapy switched to ticagrelor (T) (Figure 1a ). Methods: During working hours, Multiple Electrode Aggregometry (MEA) was used to assess ADP-induced platelet aggregation at the end of the index procedure. The effect of P2Y12 agents on MACE and major bleeding outcomes was assessed in all patients. Multiple logistic regression was used to adjust for baseline differences. Results: With MEA data from 469 patients, Pr therapy resulted in greater suppression of platelet aggregation - 1b. In the entire study population Pr therapy was associated with reduced MACE. After adjustment there were no significant differences in the rates of MACE or major bleeding - 1c. Conclusion: Patients who received Pr (rather than C or T) had greater suppression of ADP-induced aggregation at the end of the procedure. After adjusting for baseline characteristics, these results were not associated with significant differences in clinical events.